Developmental Status of Toddlers with Stunting - Sulistiyo, Agung Rahmat; Hastuti, Apriyani; Fani, Rifatul; Kurniawan, Ardhiles Wahyu (Jurnal Keperawatan Muhammadiyah, 2026)
Background: The development of children who experience stunting is slower than the development of normal toddlers. Developments in this case, include gross motor, fine motor, social independence and language. This study aims to determine the development of children under-five years who experience stunting in the Public Health Center in Malang Regency. Research method The research design in this research is a descriptive study with a cross-sectional design approach. This research was conducted on 72 children under-five years in the Tajinan Public Health Center, Malang Regency, which was carried out in June- July 2022. The research instrument was the developmental pra- screening questionnaire and growth assessment using HAZ compared with z-score table. Data analysis in this study is univariate analysis. Result The results of the study showed that most of 67% had a suspect developmental level of 48 toddlers, almost half of the toddlers 28% of the aberration development had deviations of 20 toddlers and a small proportion of toddlers 5% (4 toddlers) had a normal development. Based on the research results, it is hoped health workers and health cadres will provide health education to mothers of toddlers regarding the fulfillment of essential nutrients to support the growth and development of toddlers, besides that health workers are expected to be able to monitor and evaluate toddlers with stunting cases.